2021
DOI: 10.1007/s00520-021-06658-z
|View full text |Cite
|
Sign up to set email alerts
|

Taste, smell and mouthfeel disturbances in patients with gastrointestinal stromal tumors treated with tyrosine-kinase inhibitors

Abstract: Context Taste, smell, and mouthfeel disturbances are underrated and underreported, but important side effects of anti-cancer medication. These symptoms are associated with a lower quality of life (QoL). The prevalence and the impact of taste, smell, and mouthfeel disturbances on daily life in patients with a gastrointestinal stromal tumor (GIST) are largely unknown. Objectives This exploratory study assessed the prevalence and type of taste, smell, and mouthfeel disturbances and their impact on daily life and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In addition, evidence about olfactory disorders, such as parosmia and anosmia, is unknown. Smell disturbances were associated with other TKIs used in patients affected by GISTs: smell alterations (23%), reduced sense of smell (27%), and new unpleasant smells (20%) [ 56 ]. Furthermore, the onset of hallucinations, including visual and auditory ones, were unknown; however, the FDA multi-disciplinary review and evaluation for AVA suggests that the use of AVA could be associated with hallucinations occurring in 2.6% of patients with GISTs [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, evidence about olfactory disorders, such as parosmia and anosmia, is unknown. Smell disturbances were associated with other TKIs used in patients affected by GISTs: smell alterations (23%), reduced sense of smell (27%), and new unpleasant smells (20%) [ 56 ]. Furthermore, the onset of hallucinations, including visual and auditory ones, were unknown; however, the FDA multi-disciplinary review and evaluation for AVA suggests that the use of AVA could be associated with hallucinations occurring in 2.6% of patients with GISTs [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consenting study participants were called three weeks after COVID-19 diagnosis to fill in a questionnaire (CRF-04) regarding smell and taste alterations by phone. The questionnaire was based on a previously used questionnaire which was designed to study taste and smell disturbances in patients with gastrointestinal stromal tumors treated with tyrosine-kinase inhibitors [ 48 ]. The questionnaire was adjusted to study COVID-19 patients.…”
Section: Methodsmentioning
confidence: 99%
“…This includes food choices (preferences and avoidance), food intake, and eating experience [ 11 ]. It was shown that sensory alteration was correlated to lower energy intake and higher weight loss, contributing to declined nutritional status and quality of life of advanced HNC patients and patients with gastrointestinal stromal tumours [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%